PENGARUH RASIO UTANG, MANAJEMEN LABA, KUALITAS HASIL PEMERIKSAAN DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Property & Real Estate di Bursa Efek Indonesia Periode 2011-2013) - -, Sulistyo; -, Kennedy; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to obtain empirical evidence about the influence of leverage, earning management, quality of audit and firm size at quality of the financial statements are measured by an index of conservatism. The populations was property & real estate companies listed on the Stock Exchange 2011-2013 period. Determination of thesample is done by using purposive sampling method based on secondary data from financial reports that are available in the Indonesia Stock Exchange Website. There were about 96 companies selected ad the sample of the study. The method of analysis used was multiple linear regression analysis. The results of this study found that: Leverage and firm size has positive significant effect on the quality of financial statements, Earning management has negative significant effect on the quality of financial statements, Quality of audite not has effect on the quality of financial statements.Keywords: financial statements, leverage, earning management, audite and firm size